A STUDY OF TEACHER TALK IN CLASSROOM INTERACTION AT AN ISLAMIC SENIOR HIGH SCHOOL - Nur Wasi'ah (IAIN MADURA, 2016)
This study investigated interactional features performed by English teacher during teaching learning process in classroom interaction, how the teacher performed it, and how interactional features helped the teacher to achieve pedagogic goal. This study used descriptive qualitative method. The data was collected by using audio-video recording and field notes. The result showed that the English teacher performed eleven interactional features out of fourteen in the classroom those are scaffolding, direct repair, content feedback, extended wait-time, seeking clarification, confirmation check, teacher echo, teacher interruption, extended teacher turn, display question and extended learner turn. Related to pedagogic goal, only teacher interruption did not help the teacher in achieving any pedagogic goal.